Defending corner kicks: Analysis from the English Premier League - Pulling, C.; Robins, M.; Rixon, T. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study was to explore tactical behaviour when defending corner kicks within the English Premier League. Specifically, the types of marking and defensive players positioned at the goalposts were investigated. A total of 436 corner kicks from 50 English Premier League games were analysed. The most commonly used marking system was one-to-one marking (90.1% of total corners), with zonal marking being used less often (9.9% of total corners). There was no significant association between the marking set-up and the number of attempts at goal conceded when defending corner kicks (p>0.05). However, teams who applied zonal marking conceded fewer goals and fewer attempts at goal than teams who used one-to-one marking. The most common set-up for defenders positioned at the goalposts was having a defender positioned only on the far post (47.3% of total corners). There was no significant association between the positioning of defensive players at goalposts and the number of attempts at goal conceded when defending corner kicks. A further detailed analysis of defending corner kicks is still required and suggestions have been made for future studies.